PEMANFAATAN INSENTIF PAJAK DI MASA PANDEMI COVID-19 PADA USAHA MIKRO KECIL DAN MENENGAH - Rio, Widya Andasari (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2024)
Utilization of tax incentives during the Covid-19 pandemic in micro, small and medium enterprises in onlineshop media on social media in Ternate City. The purpose of this study was to determine and analyze the utilization of MSME tax incentives in Ternate City during the Covid-19 pandemic. This research uses a qualitative method with a phenomenological approach, with a total of four informants from MSMEs in Ternate City. Data collection techniques by means of observation, interviews and documentation. Data testing techniques using triangulation. The results showed that in the utilization of tax incentives there are several obstacles that allow MSMEs in Ternate City not to take advantage of the final income tax incentive borne by the government. However, with the existence of drivers, Ternate City MSMEs continue to take advantage of tax incentives during the pandemic and the perspective of MSMEs shows that the utilization of tax incentives can reduce the tax burden during a pandemic, can maintain business continuity, and there are MSMEs that are less interested in tax incentives, and are less effective in maintaining business.